The effect of corporate social responsibility, activity ratio, and capital structure on profitability of companies listed in the Jakarta Islamic Index - Santoso, Taufiq Agus; Andriansyah, Yuli; Bastanifar, Iman (Universitas Islam Indonesia, 2024)
IntroductionCorporate profitability remains a critical focus for businesses operating within Islamic finance frameworks, where ethical and financial principles coexist. This study examines the influence of Corporate Social Responsibility (CSR), capital structure, and activity ratio on the profitability of companies listed on the Jakarta Islamic Index (JII) from 2012 to 2017. The study aims to clarify the complex interactions among these variables and their implications for financial performance in Sharia-compliant firms.ObjectivesThe primary objective of this research is to analyze the individual and collective effects of CSR, capital structure, and activity ratio on profitability, measured by Return on Equity (ROE). The study seeks to provide actionable insights for managers and policymakers in Islamic finance, while contributing to the academic discourse on corporate performance determinants.MethodThis quantitative study employs secondary data from the financial statements of 13 JII-listed firms over five years. CSR is measured through Islamic Social Reporting, capital structure by Debt-to-Equity Ratio, and activity ratio by Total Asset Turnover. Multiple regression analysis using econometric tools tests the hypotheses, supported by descriptive and inferential statistical methods.ResultsThe findings reveal that CSR does not have a direct significant impact on profitability, while capital structure negatively influences financial performance due to risks associated with debt. Conversely, activity ratio positively affects profitability, highlighting the importance of operational efficiency. Collectively, these variables significantly shape financial outcomes in Sharia-compliant firms.ImplicationsThe study underscores the need for an integrated approach to balancing ethical commitments, financial strategies, and operational practices to achieve sustainable profitability. The findings provide valuable guidance for improving corporate strategies in Islamic finance and advancing the field’s literature.Originality/NoveltyThis research uniquely integrates CSR, capital structure, and activity ratio within the context of JII-listed firms, offering a comprehensive perspective on profitability dynamics in Islamic finance. It contributes to both theoretical and practical understandings of financial performance in Sharia-compliant businesses.